2009
DOI: 10.1002/anie.200804198
|View full text |Cite
|
Sign up to set email alerts
|

Unique Identification of Supramolecular Structures in Amyloid Fibrils by Solid‐State NMR Spectroscopy

Abstract: The fibril structure formed by the amyloidogenic fragment SNNFGAILSS of the human islet amyloid polypeptide (hIAPP) is determined with 0.52 A resolution. Symmetry information contained in the easily obtainable resonance assignments from solid-state NMR spectra (see picture), along with long-range constraints, can be applied to uniquely identify the supramolecular organization of fibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
186
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 12 publications
18
186
0
2
Order By: Relevance
“…homo and hetero), and direction of β strands themselves (i.e. co-aligned and anti-aligned), as shown by Neilson et al [8]. To investigate the relationship between structural compositions based on the organization of each β strand, we considered four basic kinds of polymorphic structures: antiparallel hetero (APHE), antiparallel homo (APHO), parallel hetero (PHE) and parallel homo (PHO) (see Fig.…”
Section: Construction Of Polymorphic Hiapp Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…homo and hetero), and direction of β strands themselves (i.e. co-aligned and anti-aligned), as shown by Neilson et al [8]. To investigate the relationship between structural compositions based on the organization of each β strand, we considered four basic kinds of polymorphic structures: antiparallel hetero (APHE), antiparallel homo (APHO), parallel hetero (PHE) and parallel homo (PHO) (see Fig.…”
Section: Construction Of Polymorphic Hiapp Structuresmentioning
confidence: 99%
“…films and angled layer structures) with hierarchical compositions of β strands [5]. The existence of amyloid fibrils in these forms can be referred to as polymorphism along with the various compositions and directions of β strands [6][7][8]. Furthermore, the thickness variation of amyloid fibrils as well as the number of protofibril structure were observed [9].…”
mentioning
confidence: 90%
“…3(a)) can be ruled out by these results. It should be noted that the fibril structure of this seeded polymorph is distinct from the fibril structure of the same peptide described by Nielsen et al, [25] illustrating that the polymorphic behaviour of hIAPP 20 -29 is highly sensitive to the growth conditions.…”
Section: Application Of the Methods For The Structural Analysis Of Hiamentioning
confidence: 90%
“…Although ssNMR data support anti-parallel stacking for several amyloid fibrils [31,196,220,221], parallel in-register stacking has been experimentally demonstrated in 1998 using MAS ssNMR by Benzinger et al [222] and has since proven to be the more common architecture found in amyloid fibrils [121]. In the optimal case, when the structural homogeneity is high enough to allow for the observation of a single, highly ordered polypeptide conformation, the combination of high-resolution multidimensional ssNMR spectroscopy with different labeling approaches can serve to determine the atomic structures of amyloid fibrils.…”
Section: Applications To Structure Determination Of Amyloid Fibrilsmentioning
confidence: 96%